Optimized loading of Pt single atoms from platinic acid solution and the sweet spot for activity - Dey, Sutapa; Kim, Hyesung; Zhou, Xin; Schmuki, Patrik (Nanoscale, 2025)
In recent years, platinum single atoms (SAs) have emerged as exceptionally efficient co-catalysts for photocatalytic hydrogen (H2) evolution. In the present work, we systematically investigate the solution parameters that govern the deposition of Pt SAs from dilute H2PtCl6precursors onto well-defined sputtered anatase TiO2thin films and evaluate the effect on photocatalytic H2evolution. We show that both precursor concentration and solution composition critically determine the oxidation state, dispersion, and reactivity of surface-bound Pt species. Ultra-dilute, additive-free solutions (0.001–0.005 mM) enable strong electrostatic adsorption (SEA) and aquation-assisted anchoring of isolated Pt2+atoms, leading to atomically dispersed Pt–O–Ti surface motifs with maximal H2evolution per Pt. In contrast, increased ionic strength or unfavorable speciation caused by higher concentration or pH adjustment induces non-selective uptake, formation of Pt(iv)-rich 2D rafts, and diminished catalytic performance. Overall, we show that the placement and photocatalytic activity of Pt SAs are dictated by the pre-reaction deposition chemistry. From a practical view, this study defines a narrow yet actionable parameter window for scalable, efficient SA co-catalyst decoration and establishes the mechanistic basis for performance optimization via precursor-chemistry design.
CRIS-Team Scopus Importer:2025-12-05